Understanding informal financing - Allen, Franklin; Qian, Meijun; Xie, Jing (Journal of Financial Intermediation, 2019)
This paper offers a framework to understand informal financing based on mechanisms to deal with asymmetric information and enforcement. We find that constructive informal financing such as trade credits and family borrowing that relies on information advantages or an altruistic relationship is associated with good firm performance. Underground financing such as money lenders who use violence for enforcement is not. Constructive informal financing is prevalent in regions where access to bank loans is extensive, while its role in supporting firm growth decreases with bank loan availability. International comparisons show that China is not an outlier but rather average in using informal financing.